Evolutionary developmental biology and sustainability: A biology of resilience. Issue 4 (5th January 2021) - Gilbert, Scott F.
Abstract: Evolutionary developmental biology, and especially ecological developmental biology, is essential for discussions of sustainability and the responses to global climate change. First, this paper explores examples of animals that have successfully altered their development to accommodate human‐made changes to their environments. We next document the ability of global warming to disrupt the development of those organisms with temperature‐dependent sex‐determination or with phenologies coordinating that organism's development with those of other species. The thermotolerance of Homo sapiens is also related to key developmental factors concerning brain development and maintenance, and the development of corals, the keystone organisms of tropical reefs, is discussed in relation to global warming as well as to other anthropogenic changes. While teratogenic and endocrine‐disrupting compounds are not discussed in this essay, the ability of glyphosate herbicides to block insect development is highlighted. Last, the paper discusses the need to creatively integrate developmental biology with ecological, political, religious, and economic perspectives, as the flourishing of contemporary species may require altering the ways that Western science has considered the categories of nature, culture, and self. Abstract : Green sea turtles laying eggs on Maui. Animals whose development is responsive to environmental cues are having difficult times as the timing and strength of such cues are altered by climate changes. Numerous strategies, uniting biological and social factors, attempt to preserve species and allow them to flourish. Research Highlights: Knowledge of developmental biology is critical for discussions of sustainability and for the possibilities of multispecies flourishing. Endangered coral reefs and turtle species highlight the developmental interactions between the biotic and abiotic portions of the environment. Developmental biology must interact creatively with philosophy, economics, religion, politics in order for environmental survival.